PENGARUH LAMA PEMBERIAN ASPIRIN TERHADAP EKSPRESI KI-67 DAN KETEBALAN EPITEL MUKOSA RONGGA MULUT TIKUS GALUR WISTAR - , dian yosi arinawati ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Aspirin has been widely used as an anti-inflammatory, antipyretic, and analgesics Aspirin has been widely used as an anti-inflammatory, antipyretic, and analgesics drugs. It has seriously side effects like gastrointestinal ulceration, delayed healing ulcer, and oral mucosal ulceration when Aspirin is administered for long time. The aim of this study was to examine the effect of Aspirin administration on Kiehl-67 (KI-67) protein expressions and oral mucosall epithelial thickness in male Wistar mice. Experimental laboratoric study with post-test only control group design was performed in this study. Forty male Wistar mice were used in this experiment. All of samples were divided into 2 groups. Group I was treated with Aspirin, whereas group II was receive aquadest. Each group was divided into 5 subgroups for assessment of the length administration effect. All of mice were sacrificed on day 1, 3, 5, 7, and 10 after treatment. Aspirin was orally administrated with doses of 9 mg/kg body weight. The buccal right of mice oral mucosal tissue was sliced and delivered for immunohistochemistry staining using anti-KI-67. Hematoxylin-eosin (HE) staining was performed to measure the oral epithelial thickness. Examination of KI-67 expressions and oral epithelial thickness were performed by using ImageJ software. Two-way Anova and Kruskall-Wallis test were carried-out for data analysis with significant level of 95%. The results revealed that the administration of Aspirin in mice on day 1, 3, 5, 7, and 10 was markedly decreased in the KI-67 protein expressions and oral epithelial thickness compared with that of control (p<0.05), otherwise the duration of Aspirin administration did not affect mucosal epithelial thickness. Aspirin administration length has the potential to suppress the KI-67 protein expression within 10 days